Paradigme ou modèle : les héritiers de Van Gogh et les paradoxes de l’authenticité - Heinich, Nathalie (RACAR : Revue d'art canadienne / Canadian Art Review, 1999)
Vincent van Gogh is still considered today as the exemplary figure of the modern artist. His works and his distinctive fate are still the object of a veneration to which a considerable market value is linked. This article examines the paradox originating from the status given to van Gogh of the “grand singulier” – the great singularity – a status which remains by definition impossible to emulate. The imitation of van Gogh's art would, of course, bring about a loss of originality. Moreover, the imitation of his life as an unwilling martyr of art could only be accomplished with a loss of authenticity. This explains why allusions to van Gogh by contemporary artists such as Robert Motherwell, Gina Pane and Christian Boltanski are reduced to borrowing the distant forms of reserve, of parodic reference and of reflexive distance.